Oil and Natural Gas Management Policy in Realizing Equal Energy in Indonesia - Fatma Ulfatun Najicha (Lembaga Contrarius Indonesia, 2021)
In its development, the management of oil and gas in Indonesia has undergone several policy developments. The enactment of Law Number 22 of 2001 concerning Oil and Gas has become a new chapter in the regulation of oil and gas in Indonesia. This law wants to emphasize that national development must be directed to the realization of people's welfare by carrying out reforms in all fields of national and state life. This article finds that the law has affirmed the objectives of natural gas management to increase state income, create jobs, improve the welfare and prosperity of the people in a just and equitable manner, and maintain the environmental sustainability. However, gas management must be carried out carefully and should be free from liberalization schemes that can bring about social injustice and failure to achieve people's welfare. The Constitutional Court's decision, which has annulled the articles in the law, is imperative to do the legal reconstruction by ensuring laws that create happiness for the people.Keywords: Oil; Natural Gas; Equal Energy; Management Policy.